A festa do vaqueiro de Porto da Folha : cordelizando vamos ensinando a história e estudando o alto sertão sergipano - Goveia, José Abraão Rezende (2022)
The festivities, over time, have been part of the history of the Brazilian population, with their rituals, symbolisms, traditions, customs, structures, their meanings and (re)meanings, changes and continuities, continuities and transformations, these have been celebrated and conveying diverse social and cultural experiences. The objective of this work is to provide, to students in the final years of elementary school, knowledge about the Festa do Vaqueiro in Porto da Folha-SE, relating this event to a historical construction in time, as well as in an interdisciplinary way. In view of this proposal, a field research was carried out between 2020 and 2021 on the aforementioned party, in order to seek to understand its organization and dynamics during the 49 years of its existence. With that, we carried out a documentary survey through Sociedade Recreativa Parque Nilo dos Santos, which organizes the party, through its regiment, minutes of meetings, attendance lists, membership sheets of the entity, an interview, and dialogues with some of its members, some city residents, students and religious leaders of the municipality, that is, we carried out a survey of records photographs in the aforementioned entity - among its members and former residents, in the parish and in the municipal government -, and we analyzed the legislation of the Festa do Vaqueiro at the municipal and state levels, as well as we researched events about the party recorded in police reports. from Porto da Folha-SE between 2009 and 2019. In this sense, with this survey, we relate the product of this research to cordel, a practice carried out by the author of this research in his history classes, in which cordel sextiles are used to teach to your students. That said, thirty-six pages of a string booklet in a sextilla format with ilustrativos about the history of the cowboy festival in Porto da Folha-SE were produced for this work, in order to be used by students in the classroom. Regarding vaquejadas, cowboys and popular parties, theoretically we discussed with João Capistrano de Abreu (1962), Euclides da Cunha (2012), Câmara Cascudo (1984), Laura de Albuquerque Maurício (2006), José Adeilson dos Santos (2018) , Giulle Vieira da Mata (2003), Maria Luíza Coelho Cavalcanti (2017), Mary Del Priore (1994). As for local history, we pay attention to the researchers Circe Bittencourt (2009), Marcos Martins (2010), Maria Auxiliadora Schmidt (2007). We also analyzed the BNCC and articulated its objects of knowledge to the Festa do Vaqueiro in Porto da Folha-SE and to the use of cordel in the classroom, as part of the experiences of our students, in which they can understand concepts, problematize and value their stories and develop a critical sense in face of their social, economic, cultural and historical reality.